Lidija Ose (Osis) – Architect of Standard Residential Buildings and Furniture Designer - Gudro, Ilze (History of Engineering Sciences and Institutions of Higher Education, 2024)
The article summarizes for the first time information about Lidija Ose (1922–1985), an architect of Soviet-era standard (typical) residential buildings and designer of built-in furniture, a graduate of the Faculty of Architecture of the Latvian State University (1952). It reflects the architect’s life and education, as well as her creative contribution during the period from the mid-1950s to the late 1970s when massive residential development took place and new standard multi-storey residential buildings were designed. The architect has contributed to the design, development, and construction of buildings of series M2, M3, 1-430, 1-316, 1-318, 103, 104, 119, and 467. L. Ose has also designed built-in kitchens, bathrooms, hallway furniture, building entrances, and interior and architectural elements (windows, balconies, doors, and their technical and structural details). Her work also includes cultural centres, clubs, cinemas, and a student dormitory. L. Ose has participated in several architectural design competitions, including for a sports centre on Lucavsala. Together with architects Marta Staņa (1913–1972), Imants Jākobsons (1934–1993), and Harolds Kanders (1927–2004), she participated in the design of the new building of the Daile Theatre at 75 Brīvības (then – Ļeņina) Street.